2016
DOI: 10.1002/adhm.201500845
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Surface Nanotopography and Chemistry on Primary Neutrophil and Macrophage Cellular Responses

Abstract: Synthetic materials employed for enhancing, replacing, or restoring biological functionality may be compromised by the host immune responses that they evoke. Surface modification has attracted substantial attention as a tool to modulate the host response to synthetic materials; however, how surface nanotopography combined with chemistry affects immune effector cell responses is still poorly understood. To address this open question, a unique set of model surfaces with controlled surface nanotopography in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 90 publications
(113 citation statements)
references
References 45 publications
3
110
0
Order By: Relevance
“…Published studies have so far shown that surface properties such as surface nanotopography and chemistry are some of the important parameters influencing immune cellular reactions . It is also well documented that changes in cellular responses are associated with the concentration and conformation of serum proteins on the surface .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Published studies have so far shown that surface properties such as surface nanotopography and chemistry are some of the important parameters influencing immune cellular reactions . It is also well documented that changes in cellular responses are associated with the concentration and conformation of serum proteins on the surface .…”
Section: Resultsmentioning
confidence: 99%
“…Despite a growing interest in studying cellular responses and protein adsorption to different nanorough substrates, a mechanistic understanding of the actual role of nanostructures on surface–protein–cellular interactions is still missing and published data often appear contradictory. For instance, conflicting reports show that fibrinogen adsorption and cellular adhesion may be either encouraged or discouraged by surface nanotopography .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the degree of orientation of the macrophages increased with increasing depth and with decreasing width of grooves . Secretion of cytokines IL‐6 and IL‐1β from macrophages decreased (60 ng/ml and 4 ng/ml to 20 ng ml −1 and 2.5 ng ml −1 respectively) with increasing size of the nanoscale features (16 nm to 68 nm) . Importantly, the elongation of bone marrow derived macrophages and expression of phenotypic markers associated with a pro‐healing M2 phenotype was highest on intermediate groove sizes ranging from 400 nm to 5 µm in width …”
Section: Immune‐engineering Strategies Of Electrospun Scaffoldsmentioning
confidence: 99%
“…Several studies have indicated that the guidance (cell shape) and activation (phenotype) of macrophages are influenced by nanoscale topographical features . Macrophages can be sensitive to nanotopography as small as 30 nm .…”
Section: Immune‐engineering Strategies Of Electrospun Scaffoldsmentioning
confidence: 99%
“…Nanosized topographical features have been reported in the natural extra cellular matrix and it is now believed that only nano textures of sizes similar to those of natural proteins affect their potential denaturation . Surfaces with tailored nanotopography are being investigated as novel cell culture substrate because they can be tuned to improve cell adhesion, modulate immune response and direct stem cells differentiation into targeted lineages . Additionally, careful surface nanoengineering can also help controlling bacterial adhesion and biofilm formation .…”
Section: Why Nanotopography?mentioning
confidence: 99%